Fracture-Safe and Fatigue-Reliable Structures - M. N. James (Fracture and Structural Integrity)
Learning from history is, by popular account, something at which human beings are not particularly good; George Bernard Shaw having stated that “we learn from history that we learn nothing from history”, while the Spanish philosopher George Santayana apparently claimed that “those who cannot learn from history are doomed to repeat it”.1 This is certainly true in the field of structural integrity where, some 150 years after the first full-scale structural fatigue tests were carried out, fracture-safe and fatigue-reliable design can be achieved to a statistical probability in complex and sophisticated structures, such as aircraft. Alongside this, however, failures of large, and expensive, welded structures can still occur from such simple causes as inadequate communication, and lack of awareness of the importance of the design of structural details to the overall fatigue life and failure. This paper considers several examples of such difficulties in the context of the development of fatigue design philosophies and the success or otherwise of learning from the history of failures.